SYNTHESIS OF MALEIL ACETATE THROUGH ESTERIFICATION REACTIONS OF MALIC ACID USING ANHYDRATE ACETATE - Muhammad Rifky Rizqullah; Daniel -; Eva Marliana (Jurusan Kimia FMIPA UNMUL, 2021)
Research has been carried out on the synthesis of maleil acetate through esterification reactions of malic acid using anhydrate acetate. Esterification of malic acid was carried out with a ratio of anhydrate acetate 1:2 to produce maleil acetate with a yield of 72.08%. The formed maleil acetate then characterizes using the FT-IR instrument. The result of FT-IR analysis which will indicate that maleil acetate has formed is that the hydroxyl group from malic acid has been converted into an ester group from the esterification reaction. The wave number of the hydroxyl group of malic acid is 3448.72 cm-1 and the ester group is the result of an esterification reaction at wave number 1735.93 cm-1, indicating that maleil acetate has been formed.